Leadership in Congregations - Bass, Richard (Rowman & Littlefield Publishers, 2006)
This new book in Alban's Harvesting the Learnings Series gathers the collected wisdom of over 10 years of Alban research and reflection on what it means to be a leader in a congregation, how our perceptions of leadership are changing, and exciting new directions for leadership in the future. With pieces by such diverse church leaders as Graham Standish, Diana Butler Bass, Jeffrey Jones, Donna Schaper, Gil Rendle, Ann Svennungsen, Mark Lau Branson, and many others, this volume gathers in one place a variety of essays that approach the leadership task and challenge with insight, depth, humor, and imagination. The book also includes the full text of Alban's 2001 special report, "The Leadership Situation Facing American Congregations" by James P. Wind and Gil Rendle. That report examined the evidence for turmoil on the one hand and ferment on the other. The Alban Institute, it declared, stood on the side of ferment. To live into the ferment, we need to see leadership in new ways and learn a new set of adaptive skills that allow them to shape new patterns of congregational life and new leadership roles. Based in research and experience, this volume makes available the best of Alban's learning on how the leaders of congregations can go about this important work.